Sonic hedgehog signaling in astrocytes mediates cell type-specific synaptic organization - Hill, Steven A; Blaeser, Andrew S; Coley, Austin A; Xie, Yajun; Shepard, Katherine A; Harwell, Corey C; Gao, Wen-Jun; Garcia, A Denise R (eLife, 2019)
Astrocytes have emerged as integral partners with neurons in regulating synapse formation and function, but the mechanisms that mediate these interactions are not well understood. Here, we show that Sonic hedgehog (Shh) signaling in mature astrocytes is required for establishing structural organization and remodeling of cortical synapses in a cell type-specific manner. In the postnatal cortex, Shh signaling is active in a subpopulation of mature astrocytes localized primarily in deep cortical layers. Selective disruption of Shh signaling in astrocytes produces a dramatic increase in synapse number specifically on layer V apical dendrites that emerges during adolescence and persists into adulthood. Dynamic turnover of dendritic spines is impaired in mutant mice and is accompanied by an increase in neuronal excitability and a reduction of the glial-specific, inward-rectifying K+ channel Kir4.1. These data identify a critical role for Shh signaling in astrocyte-mediated modulation of neuronal activity required for sculpting synapses.
Keywords: astrocyte; synapse; Sonic hedgehog; plasticity; development; spines